2021
DOI: 10.3390/ijerph18136849
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Episodic and Semantic Autobiographical Memory in aMCI and Alzheimer’s Disease Patients

Abstract: Background: The main objective of this study was to analyze the evolution of autobiographical memory (both episodic and semantic) in patients with mild cognitive impairment, patients with Alzheimer’s disease, and a healthy control group. We compared these groups at two time points: first, at baseline, and in a follow-up after 18 months. Method: Twenty-six healthy older adults, 17 patients with mild amnestic cognitive impairment, and 16 patients with Alzheimer’s disease, matched on age and educational level, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Fourteen studies out of twenty-one have studied this aspect, while seven articles [26,32,[34][35][36][37][38] focused only on the episodic component. Among the 14 articles that analyzed autobiographical semantic memory, 4 of them [21,24,29,33] have not found any significant differences in semantic memory scores between patients with MCI and healthy controls. On the other hand, seven studies [22,23,25,28,30,31,39] have found a worse semantic performance in patients with MCI when compared to the HC group.…”
Section: Episodic and Semantic Autobiographical Memorymentioning
confidence: 97%
See 2 more Smart Citations
“…Fourteen studies out of twenty-one have studied this aspect, while seven articles [26,32,[34][35][36][37][38] focused only on the episodic component. Among the 14 articles that analyzed autobiographical semantic memory, 4 of them [21,24,29,33] have not found any significant differences in semantic memory scores between patients with MCI and healthy controls. On the other hand, seven studies [22,23,25,28,30,31,39] have found a worse semantic performance in patients with MCI when compared to the HC group.…”
Section: Episodic and Semantic Autobiographical Memorymentioning
confidence: 97%
“…Attrition and reporting biases posed low risks in all of the included studies. Instead, sample bias risk was high in six articles [15,[29][30][31][32][33], due to the lack of demographic information (e.g., female ratio, mean age, mean years of schooling). Moreover, measurement bias risk was high in eight studies due to the use of non-validated or ad hoc tasks to measure autobiographical memory.…”
Section: Studies' Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation